PERAN GELAR ADAT SAI BATIN DALAM STRUKTUR SOSIAL DAN PELAKSANAAN UPACARA ADAT PADA MASYARAKAT DESA WAY EMPULAU ULU - wijaya, rolim (Studi Budaya Nusantara, 2021)
In the village of way empulau ulu, the status and roles of each individu are called in a society called the sai inner's tribal title. The traditional title of sai batin holds a central role in the social structure and ritualistic practice in the village of way empulau ulu. The study uses a descretive qualitative approach. Studies are carried out in the village of way empulau ulu, in the districts balik bukit, Lampung barat, in the Lampung province, study to kepaksian sekala berak paksi buay bejalan di way dan nyerupa . Research has shown that (1) the role of the title adat sai batin in social structure is to regulate socialized and socialized processes and manage communities to respect each other. (2) in the performance of the traditional ceremony the title adat sai batin funcion to, control and planning of various performing rituals to be performed. (3) induvidu who has earned his degree adat have to understand its function and duties in kebot and society so as not to create new problems in kebot and society.